2016
DOI: 10.1108/ijbm-04-2015-0056
|View full text |Cite
|
Sign up to set email alerts
|

Consumer preferences for banking technologies by age groups

Abstract: Purpose – The prevailing mindset is that younger people value and more readily adopt technology. The purpose of this paper is to determine if this is true with respect to banking practices. Design/methodology/approach – A survey was conducted to evaluate the importance of mobile, online, and physical-based banking across multiple age groups. Factor analysis and analysis of covariance were used to evaluate the responses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 34 publications
1
48
2
1
Order By: Relevance
“…In line with Tam and Oliveira (2016), Hew et al (2015), and Malaquias and Hwang (2019), the results of moderation analysis complements the previous findings of insignificant role of gender in mobile banking context. Interestingly, even though Harris et al (2016) found that young users are more attached to new technologies, our results indicated that there was no significant differences across age groups in mobile banking, being in line with Malaquias and Hwang (2019). Perhaps, elder people are becoming more tech-savvy and the mobile penetration ratio is increasing rapidly.…”
Section: Results Of Nonlinear Relationshipscontrasting
confidence: 54%
See 1 more Smart Citation
“…In line with Tam and Oliveira (2016), Hew et al (2015), and Malaquias and Hwang (2019), the results of moderation analysis complements the previous findings of insignificant role of gender in mobile banking context. Interestingly, even though Harris et al (2016) found that young users are more attached to new technologies, our results indicated that there was no significant differences across age groups in mobile banking, being in line with Malaquias and Hwang (2019). Perhaps, elder people are becoming more tech-savvy and the mobile penetration ratio is increasing rapidly.…”
Section: Results Of Nonlinear Relationshipscontrasting
confidence: 54%
“…H12: Satisfied users will continue using the apps in online banking transactions. Harris et al (2016) found that young users are attached to new technologies compared to older consumers who are more interested in traditional banking. The results of the study by Tam and Oliveira (2016) also indicated a significant differences across age groups where degree of use was more important to older users in mobile banking adoption in Portugal.…”
Section: H11mentioning
confidence: 99%
“…As in other studies dealing with banking digitalization, the primary data for this study were collected from a consumer survey (see among others Asadi et al, 2017;Gerrard et al, 2006;Harris et al, 2016;Laukkanen, 2016;Venkatesh and Bala, 2008). The survey was conducted specifically for this research in November and December 2016 in Spain.…”
Section: Datamentioning
confidence: 99%
“…Specifically, age seems to be a relevant factor in explaining customers' digitalization. Harris et al (2016) have found that although consumers of all ages are equally interested in currently emerging technologies such as online banking, younger users are more interested in the newest technologies. Young people are also early adopters of online banking (Estrella-Ramon et al, 2016;Laforet and Li, 2005;Luo et al, 2010).…”
mentioning
confidence: 99%
“…Further, attitude is used as a moderator in the relationship between individual factors and user behaviour based on the Unified Theory of Acceptance and Use of Technology. lIterature revIew and research hypothesIs E-banking has simplified financial transactions through different technological platforms, whether it is an automated teller machine (ATM), computer, mobile phone or tablet in order to access information on a customer's account via electronic service (online service) (Harris et al, 2016;Butt & Aftab, 2013), instead of a visit to a brickand-mortar banking branch (offline service) (Daniel, 1999;Lee & Lee, 2000).The necessity of E-Banking services with the new generation's lifestyle today is reached by different levels of technology innovations (Khan, 2018;Chawla & Joshi, 2017;Aljanabi & Dileep, 2012;Rahomee et al, 2014;Aljanabi & nor azila, 2015aAljanabi & nor azila, , 2015bAlkhaffaf & Abdulqadir, 2016;Mohd Noor & Abdulqadir, 2016;Aljanabi & Dileep, 2013). E-banking provides self-service technologies in an electronic environment (Shih & Fang, 2004;Hoehle et al, 2016).Moreover, it is quite obvious that an E-banking system goes up against the traditional banking system (offline banking) (Floh & Treiblmaier, 2006;Kingshott et al, 2018) for many reasons, such as cost (Luarn & Lin, 2004;Abrahão et al, 2016), time (Hanafizadeh & Khedmatgozar, 2012), knowledge of IT (Mallat et al, 2009;Luo et al, 2010) geographic expanse, pollution, traffic jams, parking problems, saving trees (paperless transactions), for better management (Claro &Rosa, 2016), attracting more customers (Mann & Sahni, 2012) through different communication channels such as social media, mass media (Tran & Corner, 2016), e-service (Al-Qeisi & Hegazy, 2015) and financial performance of community banks (Acharya et al, 2008).…”
Section: Yadgar Taha M Hamakhanmentioning
confidence: 99%